In Vitro Evaluation of Controlled Release Bucoadhesive Tablet Formulations Containing Verapamil Hydrochloride - Özalp, Betül; Özalp, Koray (Fırat University, 2003)
Aim: The aim of this study was to prepare buccal bioadhesive tablets which have controlled release on increasing the bioavaibility and eliminating the first pass effect of verapamil. Material and method: In this study, carbopol 910 for its bioadhesive property and HPMC K4M for controlling the release of active substance have been selected as test polymers. The release of active substance from bucoadhesive verapamil tablets has been investigated by dissolution rate studies in vitro. The bioadhesive power of the tablets has been assessed by Zwick, an instrument which measures the tensile strenght. Results: As a result of the dissolution rate studies, it has been found that release profiles are affected by HPMC K4M which is a release controller agent. When bioadhesive properties are investigated, a decrease is determineted in bioadhesive power parallel to the percent of HPMC K4M. In the formula which was closer to the target profile the ratio of HPMC K4M was found 70 percent. Conclusion: It has been determined in vitro that the prepared buccal bioadhesive tablets which contain verapamil HCL can be used for therapy.

Amaç: Bu çalışmada verapamilin ilk geçiş etkisinin ortadan kaldırılması ve biyoyararlanımın arttırılabilmesi için kontrollü salım yapan bukkal biyoadheziv tabletlerinin hazırlanması amaçlanmıştır. Gereç ve yöntem: Çalışmada biyoadheziv özelliğinden dolayı, karbopol 910 ve etken madde çıkışını kontrol etmek amacıyla, hidroksipropilmetilselüloz (HPMC) K4M test polimeri olarak seçilmiştir. Bukoadheziv verapamil tabletlerinden etken madde açığa çıkışı in vitro olarak çözünme hızı deneyleriyle incelenmiştir. Tabletlerin biyoadheziv güçleri, Zwick adı verilen gerilim ölçüm cihazı kullanılarak tayin edilmiştir. Bulgular: Çözünme hızı deneyleri sonucunda salım profillerinin formulasyona giren salım kontrol edici ajan HPMC K4M'ın oranından etkilendiği bulunmuştur. Biyoadheziv özellikler incelendiğinde HPMC K4M'in yüzdesine paralel olarak biyoadhezyon kuvvetinde azalma gözlenmektedir. Amaç çıkış hızına en yakın çıkış gösteren formülde HPMC K4M oranı %70 olarak bulunmuştur. Sonuç: Hazırlanan verapamil hidroklorür içeren bukkal biyoadheziv tabletlerin tedaviye yönelik olarak kullanılabileceği in vitro olarak saptanmıştır.
Verapamil Hidroklorür İçeren Kontrollü Salım Yapan Bukoadheziv Tablet Formülasyonlarının İn Vitro İncelenmesi